EXPERT-ANALYTICAL ASSESSMENT OF INFORMATION RISKS AND THE LEVEL OF EFFICIENCY OF THE INFORMATION SECURITY SYSTEM - Arkhipov, A. E. (Radio Electronics, Computer Science, Control, 2024)
In this paper some features of information risk methodology application for information systems security research, in particular practical estimation approaches of the quantity indicators used for calculation information risk, and also parameters of information systems security and efficiency of information protection systems are considred.